Alternatives to mucuna for soil fertility management in southern Benin: farmer perception and use of traditional and exotic grain legumes - Schulz, S.; Honlonkou, A.N.; Carsky, R.J.; Manyong, Victor M.; Oyewole, B.D. (Cambridge University Press, 2003)
In southern Benin, the legume cover crop ´ Mucuna pruriens var. utilis has been widely promoted for soil fertility improvement. Recent findings have shown, however, that the majority of farmers have not adopted it, and that alternative technologies are needed that are both attractive to farmers and beneficial in terms of soil fertility. A survey was carried out in southern Benin to determine farmer perception and use of traditional ´ grain legumes and to assess the adoption potential of new low-harvest-index grain legumes. Grain legumes were shown to be integral components of traditional cropping systems and constituted farmers' most important technology for soil fertility maintenance. More than 80% of respondents expressed interest in testing new, low-harvest-index varieties. Preferred grain characteristics and farmers' culinary preferences for grain legumes varied between locations and need to be taken into account if new germplasm is to be introduced. It is argued that farmers' interest and experience in legume cultivation provide an opportunity for the introduction of alternative legume-based technologies such as low-harvest-index grain legumes and techniques for the detoxification of mucuna seed. In addition, efforts should be made to increase the productivity of current legume production systems and to develop mucuna cultivars with reduced L-dopa content. .